The Affect Factors of Earning Management (Case Study on Manufacturing Companies Listed on IDX) - M Mujiyati; Kiky Fatmawati; Kurnia Rina Ariani (Urecol Journal. Part B: Economics and Business, 2022)
Research on earnings management is very interesting to the attention of researchers, because the results of several previous studies are very diverse, so assumptions and restrictions on the object of research are needed. This study examines the effect of free cash flow, profitability, leverage, firm size, and growth on earning management. The research population was the manufacturing company of metal and the similar sub-sector listed on the Indonesia Stock Exchange in 2017-2020. The sample documentation used a purposive sampling method and obtained ten companies with 40 annual financial statement observations based upon the sample criteria. This research statistically showed that free cash flow, profitability, and growth influence earnings management by using multiple regressions. Meanwhile, leverage and firm size do not influence earning management.